2016
DOI: 10.22329/il.v36i1.4357
|View full text |Cite
|
Sign up to set email alerts
|

Developing Critical Thinking with Debate: Evidence from Iranian Male and Female Students

Abstract: This study investigates the difference between the performance of Iranian male and female EFL learners on the five dimensions of the California Critical Thinking Skills Test. Eighty-eight learners, out of 120, selected through a convenience sampling method, participated in this study. The researcher used a quantitative research method with one-group pretest posttest design. This group received "the Meeting-House Debate" strategy. Data analysis involved descriptive and inferential statistics. Results showed no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Participating in debating activities enhanced students' capacity to reason and defend topics relevant to their subject areas, as discovered by Mike, Berkowitz, Hunt, and Louden (1999). According to Bellon (2000), Tous, and Haghighi (2016), critical thinking is one of the most essential skills because it compels students to engage in rigorous thought processes in an effort to establish connections between phrases and concepts that give them a deeper level of significance. Overall, the students saw the classroom discussion as a beneficial educational exercise.…”
Section: Abilities In Analyzingmentioning
confidence: 99%
“…Participating in debating activities enhanced students' capacity to reason and defend topics relevant to their subject areas, as discovered by Mike, Berkowitz, Hunt, and Louden (1999). According to Bellon (2000), Tous, and Haghighi (2016), critical thinking is one of the most essential skills because it compels students to engage in rigorous thought processes in an effort to establish connections between phrases and concepts that give them a deeper level of significance. Overall, the students saw the classroom discussion as a beneficial educational exercise.…”
Section: Abilities In Analyzingmentioning
confidence: 99%
“…Some of this evidence is related to nursing [17], occupational therapy [18], sociology [19,20], athletic training education [21], dental education [22,23], marketing [24] or accounting [25], but it is a method rarely used in engineering subjects, a fact that this paper intends to mitigate. In addition, another study concluded that gender did not have a significant effect on the students' critical thinking skills developed with debate [26].…”
Section: Introductionmentioning
confidence: 97%